Antistatic card protection film and preparation process

By applying the glue layer of nano zinc oxide and crystal hydrate on the guard film and subjecting ultraviolet irradiation, the problem of poor antistatic performance of the guard film is solved, and the effect of significantly improving the antistatic function is achieved.

CN117645738BActive Publication Date: 2025-03-18HUIZHOU YIDU STATIONERY SUPPLIES CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311510158.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2025-03-18
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

The existing card protection film has poor anti-static performance and cannot effectively prevent static electricity.

Method used

A glue layer containing nano zinc oxide and crystal hydrate was coated on one side of the bidirectional stretched polyester base film, and an ethylene-vinyl acetate copolymer layer was coated thereon, and the antistatic properties were improved by ultraviolet irradiation.

Benefits of technology

The high conductivity of nano zinc oxide and the electron decomposition effect under ultraviolet irradiation, negative charge carriers are formed, which significantly improves the anti-static function of the card protection film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses an antistatic card protection film and a preparation process thereof, which specifically comprises the following steps: coating a glue layer containing nano zinc oxide and crystal hydrate on one side of a biaxially stretched polyester base film, coating an ethylene-vinyl acetate copolymer layer on the glue layer to obtain a composite film, and then subjecting the composite film to ultraviolet irradiation treatment to obtain the antistatic card protection film. The card protection film of the present invention has a glue layer containing nano zinc oxide and crystal hydrate sprayed between the polyester base film and the EVA film, the nano zinc oxide has a high electrical conductivity, and under the irradiation of ultraviolet rays, in an environment with H2O molecules, it can decompose free-moving negatively charged electrons, so that the card protection film has excellent antistatic function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester films, and in particular to an antistatic card protection film and a preparation process thereof. Background Art

[0002] Card protection film, also known as laminating film. It is a high-grade sheet packaging material, made of polyester film as the base sheet, a single sheet evenly coated with adhesive, and then specially processed. Card protection film is widely used in the sealing of identity cards, driver's licenses, work permits, representative certificates, student certificates, photos, business cards, menus, drawings, etc. It has excellent properties such as moisture-proof, waterproof, anti-fading, anti-tampering, and easy to preserve for a long time. It is also crisp and beautiful, and has improved transparency. Plastic sealing film needs to be used with a laminating machine for heating. Different thicknesses need to refer to different plastic sealing temperatures, which are related to the pressure and speed of the laminating machine and the thickness of the plastic sealing film. When sealing and protecting various sheet materials, card protection film can provide good protection, making these materials waterproof, anti-tampering, moisture-proof, anti-insect, anti-mildew, corrosion-resistant, etc., and it is crisp and beautiful, and easy to preserve for a long time.

[0003] The prior art records a process for manufacturing a card protection film by using a BOPET polyester film as a base film and compounding it with an EVA vinyl acetate copolymer film layer, such as the card protection film manufacturing process described in references 1 and 2.

[0004] Reference 1: Chinese patent document with publication number CN114836144A

[0005] Reference 1 records an antistatic card protection film and its preparation process, the antistatic card protection film comprises a card protection film main body component, the card protection film main body component is provided with strip grooves near its four sides, each of the strip grooves is provided with an anti-breakage component, the anti-breakage component comprises a hollow rubber strip and an anti-bending strip fixed in the hollow part, the rubber strip is bonded and sealed in the strip groove, the length of the anti-bending strip is less than or equal to the length of the rubber strip, and the anti-bending strip is specifically a beryllium copper metal strip. An anti-breakage component consisting of a rubber strip and an anti-bending strip is added to the card protection film, when the card protection film is subjected to external force folding and compression, the rubber strip and the anti-bending strip have a certain rebound effect, thereby improving the anti-folding and compression performance of the card protection film.

[0006] Reference 2: Chinese patent document with publication number CN108394160A

[0007] Reference 2 records a high-quality card protection film with better performance and its preparation method. It is composed of a BOPET polyester film layer, a polyethylene film layer and an EVA vinyl acetate copolymer film layer in sequence. The EVA vinyl acetate copolymer film layer is provided with a permanent embossing, and the permanent embossing is a diamond lattice pattern. When the card protection films are stacked, the diamond lattice pattern allows gas to exist between the card protection films, and when used, it is easy to separate and will not stick. When the actual plastic-sealed sheet is over-laminated, the gas between the card protection films is discharged to the outside of the plastic-sealed sheet along the lattice pattern, and the bubbles will not be plastic-sealed on the surface of the plastic-sealed sheet or its edge. The preparation method of the diamond card protection film is to provide a diamond lattice convex pattern on the roller surface based on the original manufacturing process, control the relevant process parameters, and cool the roller to stretch, calender and composite trim, that is, the process is simple, reliable, and has no environmental pollution.

[0008] References 1 and 2 both record the process of manufacturing card protection film by using BOPET polyester film as base film and EVA vinyl acetate copolymer film layer. However, the technical problem to be solved by Reference 1 is to improve the problem that the card protection film usually lacks an anti-folding mechanism at the edge in the related technology. The technical problem to be solved by Reference 2 is that the card protection film has a poor laminating effect and bubbles. Neither References 1 nor 2 involve a technical solution to improve the antistatic performance of the card protection film. Summary of the invention

[0009] The purpose of the present invention is to solve the technical problem of poor antistatic performance of card protection films in the prior art and to provide an antistatic card protection film and a preparation process.

[0010] In order to solve the shortcomings of the above technical problems, the technical solution adopted by the present invention is: a preparation process of an antistatic card protection film, which specifically includes the following steps: coating a glue layer containing nano zinc oxide and crystalline hydrate on one side of a biaxially oriented polyester base film, coating an ethylene-vinyl acetate copolymer layer on the glue layer to obtain a composite film, and then treating it with ultraviolet rays to obtain the antistatic card protection film.

[0011] Furthermore, the material of the biaxially oriented polyester base film includes polyethylene terephthalate, polybutylene terephthalate or polyethylene naphthalate.

[0012] Furthermore, the longitudinal stretching ratio of the biaxially oriented polyester base film is 2.4-3.3, and the transverse stretching ratio is 2.7-3.2.

[0013] Furthermore, the raw materials of the adhesive layer also contain polyvinyl alcohol and acrylic resin.

[0014] Furthermore, the adhesive layer contains the following raw materials in parts by weight: 100-150 parts of polyvinyl alcohol, 5-10 parts of acrylic resin, 5-15 parts of nano zinc oxide, 10-15 parts of crystalline hydrate and 50-100 parts of deionized water.

[0015] Furthermore, the crystalline hydrate is MgCl2·6H2O or Ba(OH)2·8H2O.

[0016] Furthermore, the particle size of the nano zinc oxide is 15-25 μm, and the particle size of the crystalline hydrate is 50-75 μm.

[0017] Furthermore, the adhesive layer is coated by air spraying.

[0018] Furthermore, the ultraviolet irradiation treatment uses ultraviolet rays with a wavelength of 350-380 nm.

[0019] On the other hand, the present invention also provides an antistatic card protection film prepared by the above process.

[0020] The present invention has the following beneficial effects: the card protection film of the present invention is sprayed with a glue layer containing nano zinc oxide and crystalline hydrate between a biaxially stretched polyester base film and an EVA film, the nano zinc oxide has high electrical conductivity, and under the irradiation of ultraviolet rays, in an environment with H2O molecules, it can decompose freely moving negatively charged electrons, while leaving positively charged holes, when there is static electricity in the environment, these carriers will make a directional movement inside the material under the action of the electric field, thus forming an electric current, so that the card protection film has an excellent antistatic function, and the crystalline hydrate in the glue layer is dehydrated after reaching the dehydration temperature during the EVA film molding process and is located in the glue layer, providing an H2O molecule environment for the electronic decomposition of the nano zinc oxide under ultraviolet irradiation. DETAILED DESCRIPTION

[0021] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the content of the present invention is not limited to the following embodiments.

[0022] The invention relates to a preparation process of an antistatic card protection film, and the specific steps are as follows: coating a glue layer containing nano zinc oxide and crystal hydrate on one side of a biaxially stretched polyester base film, coating an ethylene-vinyl acetate copolymer layer on the glue layer to obtain a composite film, and then subjecting the composite film to ultraviolet irradiation treatment to obtain the antistatic card protection film.

[0023] In one or more preferred embodiments, the material of the biaxially oriented polyester base film comprises polyethylene terephthalate, polybutylene terephthalate or polyethylene naphthalate, which are the main components of the biaxially oriented polyester base film. Optionally, it may further comprise one or more additives known to those skilled in the art, such as antioxidants, pigments, colorants, fillers or combinations thereof.

[0024] The preparation method of the above-mentioned biaxially oriented polyester base film includes pre-crystallizing and drying the polyester slices, then melt extruding, cooling the casting, longitudinally stretching and transversely stretching, winding and slitting. Such techniques are generally known to those skilled in the art. In other embodiments, other techniques known to those skilled in the art can be used to obtain the biaxially oriented polyester base film. Generally, the polyester slices can be pre-crystallized and dried by a crystallization drying tower, the drying temperature of the crystallization drying tower can be selected from 150-180°C, the drying time can be selected from 3-5h, and the cooling casting temperature is 15-20°C.

[0025] In one or more preferred embodiments, the biaxially oriented polyester base film is oriented at a stretch ratio of 2.4-3.3 in the longitudinal direction and 2.7-3.2 in the transverse direction. It is considered that various processing parameters are suitable for stretching in the longitudinal or transverse direction, for example, the longitudinal stretching temperature is 85-95°C; the transverse stretching temperature is 110-130°C.

[0026] In one or more preferred embodiments, the material constituting the adhesive layer further includes a conductive polymer and an adhesive resin, preferably polyvinyl alcohol and acrylic resin, respectively, which can relatively improve the basic antistatic properties of the film and give the adhesive layer a certain degree of adhesion.

[0027] In one or more preferred embodiments, the adhesive layer comprising the above-mentioned substance contains the following raw materials by weight: 100-150 parts of polyvinyl alcohol, 5-10 parts of acrylic resin, 5-15 parts of nano zinc oxide, 10-15 parts of crystalline hydrate and 50-100 parts of deionized water.

[0028] In one or more preferred embodiments, the crystalline hydrate is MgCl2·6H2O or Ba(OH)2·8H2O. During the EVA film forming process, the crystalline hydrate is dehydrated after reaching the dehydration temperature and is located in the adhesive layer, providing a H2O molecular environment for the electronic decomposition of nano zinc oxide under ultraviolet irradiation.

[0029] In one or more preferred embodiments, the particle size of the nano zinc oxide is 15-25 μm, and the particle size of the crystalline hydrate is 50-75 μm.

[0030] In one or more preferred embodiments, the adhesive layer is coated by air spraying or high pressure air spraying. Without being limited by theory, other coating techniques generally known to those skilled in the art may also be selected.

[0031] In one or more preferred embodiments, the coating method of the ethylene-vinyl acetate copolymer is to flow the ethylene-vinyl acetate copolymer melt through a mold onto the surface of the adhesive layer. Without being limited by theory, other coating techniques generally known to those skilled in the art may also be selected. After the coating is completed, the composite film is obtained by roller cooling, stretching, calendering, and composite trimming, and finally subjected to ultraviolet irradiation.

[0032] In one or more preferred embodiments, the ultraviolet irradiation treatment is to use ultraviolet rays with a wavelength of 350-380nm to perform a curing treatment on the adhesive layer to obtain a cured layer.

[0033] The features of the present invention are described below by means of specific examples and comparative examples, but are not intended to limit the scope of the present invention.

[0034] <Example 1>

[0035] A preparation process of anti-static card protection film:

[0036] S1. Pre-crystallize and dry the polyester chips (polyethylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0037] Among them, the drying temperature of the crystallization drying tower is 150°C and the drying time is 5h.

[0038] The cooling temperature of the casting was 15°C; the longitudinal stretching temperature was 95°C, and the longitudinal stretching ratio was 2.4; the transverse stretching temperature was 130°C, and the transverse stretching ratio was 2.7.

[0039] S2, taking polyvinyl alcohol, acrylic resin, nano zinc oxide, MgCl2·6H2O and deionized water, stirring them evenly, and spraying them on one side of the biaxially oriented polyester base film obtained in step S1 by air spraying.

[0040] The added amount of each raw material is calculated by weight as follows: 100 parts of polyvinyl alcohol, 10 parts of acrylic resin, 5 parts of nano zinc oxide, 15 parts of crystalline hydrate and 50 parts of deionized water.

[0041] The particle size of nano zinc oxide is 15 μm, and the particle size of crystalline hydrate is 75 μm.

[0042] S3, the ethylene-vinyl acetate copolymer melt flows out through the mold to the side of the polyester base film with the spray layer in step S2, and is roller cooled, stretched, calendered, composited and trimmed to obtain a composite film.

[0043] S4, the composite film obtained in step S3 is irradiated with ultraviolet rays (wavelength 350nm) to obtain an antistatic card protection film.

[0044] <Example 2>

[0045] A preparation process of anti-static card protection film:

[0046] S1. Pre-crystallize and dry the polyester chips (polybutylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0047] Among them, the drying temperature of the crystallization drying tower is 180°C and the drying time is 3h.

[0048] The cooling temperature of the casting was 20°C; the longitudinal stretching temperature was 85°C, and the longitudinal stretching ratio was 3.3; the transverse stretching temperature was 110°C, and the transverse stretching ratio was 3.2.

[0049] S2, taking polyvinyl alcohol, acrylic resin, nano zinc oxide, Ba(OH)2·8H2O and deionized water, stirring them evenly, and spraying them on one side of the biaxially oriented polyester base film obtained in step S1 by air spraying.

[0050] The added amount of each raw material is calculated by weight as follows: 150 parts of polyvinyl alcohol, 5 parts of acrylic resin, 15 parts of nano zinc oxide, 10 parts of crystalline hydrate and 100 parts of deionized water.

[0051] The particle size of nano zinc oxide is 25 μm, and the particle size of crystalline hydrate is 50 μm.

[0052] S3, the ethylene-vinyl acetate copolymer melt flows out through the mold to the side of the polyester base film with the spray layer in step S2, and is roller cooled, stretched, calendered, composited and trimmed to obtain a composite film.

[0053] S4, subjecting the composite film obtained in step S3 to ultraviolet (380 nm) irradiation treatment to obtain an antistatic card protection film.

[0054] <Example 3>

[0055] A preparation process of anti-static card protection film:

[0056] S1. Pre-crystallize and dry the polyester chips (polyethylene naphthalate) through a crystallization drying tower, and then melt extrude, cool and cast, stretch longitudinally, stretch transversely, wind up and slit to obtain a biaxially oriented polyester base film.

[0057] Among them, the drying temperature of the crystallization drying tower is 160°C and the drying time is 3.5h.

[0058] The cooling temperature of the casting was 16°C; the longitudinal stretching temperature was 90°C, and the longitudinal stretching ratio was 3.1; the transverse stretching temperature was 120°C, and the transverse stretching ratio was 2.9.

[0059] S2, taking polyvinyl alcohol, acrylic resin, nano zinc oxide, MgCl2·6H2O and deionized water, stirring them evenly, and spraying them on one side of the biaxially oriented polyester base film obtained in step S1 by air spraying.

[0060] The added amount of each raw material is calculated by weight as follows: 120 parts of polyvinyl alcohol, 6 parts of acrylic resin, 10 parts of nano zinc oxide, 11 parts of crystalline hydrate and 80 parts of deionized water.

[0061] The particle size of nano zinc oxide is 20 μm, and the particle size of crystalline hydrate is 65 μm.

[0062] S3, the ethylene-vinyl acetate copolymer melt flows out through the mold to the side of the polyester base film with the spray layer in step S2, and is roller cooled, stretched, calendered, composited and trimmed to obtain a composite film.

[0063] S4, subjecting the composite film obtained in step S3 to ultraviolet (360 nm) irradiation treatment to obtain an antistatic card protection film.

[0064] <Example 4>

[0065] A preparation process of anti-static card protection film:

[0066] S1. Pre-crystallize and dry the polyester chips (polyethylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0067] Among them, the drying temperature of the crystallization drying tower is 170°C and the drying time is 4 hours.

[0068] Among them, the cooling temperature of the casting was 18°C; the longitudinal stretching temperature was 88°C, and the longitudinal stretching ratio was 3.2; the transverse stretching temperature was 115°C, and the transverse stretching ratio was 2.8.

[0069] S2, taking polyvinyl alcohol, acrylic resin, nano zinc oxide, MgCl2·6H2O and deionized water, stirring them evenly, and spraying them on one side of the biaxially oriented polyester base film obtained in step S1 by air spraying.

[0070] The added amounts of the raw materials are as follows by weight: 120 parts of polyvinyl alcohol, 8 parts of acrylic resin, 6 parts of nano zinc oxide, 11 parts of MgCl2·6H2O and 60 parts of deionized water.

[0071] The particle size of nano zinc oxide is 20 μm, and the particle size of crystalline hydrate is 70 μm.

[0072] S3, the ethylene-vinyl acetate copolymer melt flows out through the mold to the side of the polyester base film with the spray layer in step S2, and is roller cooled, stretched, calendered, composited and trimmed to obtain a composite film.

[0073] S4, subjecting the composite film obtained in step S3 to ultraviolet (370 nm) irradiation treatment to obtain an antistatic card protection film.

[0074] <Example 5>

[0075] A preparation process of anti-static card protection film:

[0076] S1. Pre-crystallize and dry the polyester chips (polyethylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0077] Among them, the drying temperature of the crystallization drying tower is 175°C and the drying time is 3h.

[0078] Among them, the cooling temperature of the casting was 16°C; the longitudinal stretching temperature was 92°C, and the longitudinal stretching ratio was 2.6; the transverse stretching temperature was 125°C, and the transverse stretching ratio was 3.0.

[0079] S2, taking polyvinyl alcohol, acrylic resin, nano zinc oxide, MgCl2·6H2O and deionized water, stirring them evenly, and spraying them on one side of the biaxially oriented polyester base film obtained in step S1 by air spraying.

[0080] The added amount of each raw material is calculated by weight as follows: 150 parts of polyvinyl alcohol, 10 parts of acrylic resin, 15 parts of nano zinc oxide, 15 parts of crystalline hydrate and 100 parts of deionized water.

[0081] The particle size of nano zinc oxide is 20 μm, and the particle size of crystalline hydrate is 75 μm.

[0082] S3, the ethylene-vinyl acetate copolymer melt flows out through the mold to the side of the polyester base film with the spray layer in step S2, and is roller cooled, stretched, calendered, composited and trimmed to obtain a composite film.

[0083] S4, subjecting the composite film obtained in step S3 to ultraviolet (350 nm) irradiation treatment to obtain an antistatic card protection film.

[0084] <Comparative Example 1>

[0085] A preparation process of a card protection film:

[0086] S1. Pre-crystallize and dry the polyester chips (polyethylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0087] Among them, the drying temperature of the crystallization drying tower is 150°C and the drying time is 5h.

[0088] The cooling temperature of the casting was 15°C; the longitudinal stretching temperature was 95°C, and the longitudinal stretching ratio was 2.4; the transverse stretching temperature was 130°C, and the transverse stretching ratio was 2.7.

[0089] S2, the ethylene-vinyl acetate copolymer melt flows out through a mold onto the polyester base film of step S2, and is subjected to roller cooling, stretching, calendering, composite trimming, to obtain a card protection film.

[0090] <Comparative Example 2>

[0091] A preparation process of a card protection film:

[0092] S1. Pre-crystallize and dry the polyester chips (polyethylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0093] Among them, the drying temperature of the crystallization drying tower is 160°C and the drying time is 3.5h.

[0094] The cooling temperature of the casting was 16°C; the longitudinal stretching temperature was 90°C, and the longitudinal stretching ratio was 3.1; the transverse stretching temperature was 120°C, and the transverse stretching ratio was 2.9.

[0095] S2, the ethylene-vinyl acetate copolymer melt flows out through a mold onto the polyester base film of step S2, and is subjected to roller cooling, stretching, calendering, composite trimming, to obtain a card protection film.

[0096] <Comparative Example 3>

[0097] A preparation process of a card protection film:

[0098] S1. Pre-crystallize and dry the polyester chips (polyethylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0099] Among them, the drying temperature of the crystallization drying tower is 150°C and the drying time is 5h.

[0100] The cooling temperature of the casting was 15°C; the longitudinal stretching temperature was 95°C, and the longitudinal stretching ratio was 2.4; the transverse stretching temperature was 130°C, and the transverse stretching ratio was 2.7.

[0101] S2, taking polyvinyl alcohol, acrylic resin, nano zinc oxide and deionized water, stirring them evenly, and spraying them on one side of the biaxially oriented polyester base film obtained in step S1 by air spraying.

[0102] The added amount of each raw material is calculated by weight as follows: 100 parts of polyvinyl alcohol, 10 parts of acrylic resin, 5 parts of nano zinc oxide and 50 parts of deionized water.

[0103] Wherein, the particle size of nano zinc oxide is 15 μm.

[0104] S3, the ethylene-vinyl acetate copolymer melt flows out through the mold to the side of the polyester base film with the spray layer in step S2, and is roller cooled, stretched, calendered, composited and trimmed to obtain a composite film.

[0105] S4, the composite film obtained in step S3 is irradiated with ultraviolet light (wavelength 350nm) to obtain a card protection film.

[0106] <Comparative Example 4>

[0107] A preparation process of a card protection film:

[0108] S1. Pre-crystallize and dry the polyester chips (polyethylene terephthalate) through a crystallization drying tower, and then melt extrude, cool and cast, longitudinally stretch, transversely stretch, wind up and slit to obtain a biaxially stretched polyester base film.

[0109] Among them, the drying temperature of the crystallization drying tower is 150°C and the drying time is 5h.

[0110] The cooling temperature of the casting was 15°C; the longitudinal stretching temperature was 95°C, and the longitudinal stretching ratio was 2.4; the transverse stretching temperature was 130°C, and the transverse stretching ratio was 2.7.

[0111] S2, taking polyvinyl alcohol, acrylic resin, MgCl2·6H2O and deionized water, stirring them evenly, and spraying them on one side of the biaxially oriented polyester base film obtained in step S1 by air spraying.

[0112] The added amount of each raw material is calculated by weight as follows: 100 parts of polyvinyl alcohol, 10 parts of acrylic resin, 15 parts of crystalline hydrate and 50 parts of deionized water.

[0113] The particle size of nano zinc oxide is 15 μm, and the particle size of crystalline hydrate is 75 μm.

[0114] S3, the ethylene-vinyl acetate copolymer melt flows out through the mold to the side of the polyester base film with the spray layer in step S2, and is roller cooled, stretched, calendered, composited and trimmed to obtain a composite film.

[0115] S4, the composite film obtained in step S3 is irradiated with ultraviolet light (wavelength 350nm) to obtain a card protection film.

[0116] <Mechanical Properties>

[0117] The mechanical properties of the card protection films prepared in Examples 1-5 and Comparative Examples 1-4 were tested, including tensile strength and elongation at break, and the test standard was ASTM D-882. The test results are shown in the following table:

[0118] Group Tensile strength(MPa) Elongation at break (%) Example 1 241 117 Example 2 239 124 Example 3 242 120 Example 4 241 123 Example 5 238 118 Comparative Example 1 240 118 Comparative Example 2 244 115 Comparative Example 3 236 123 Comparative Example 4 243 122

[0119] It can be seen from the above table that the mechanical properties of the card protection films in Examples 1-5 are similar to those in Comparative Examples 1-4, which indicates that the adhesive layer containing nano zinc oxide and crystalline hydrate in the present invention does not have much effect on the mechanical properties of the card protection film itself.

[0120] <Antistatic Performance>

[0121] The antistatic properties of the card protection films prepared in Examples 1-5 and Comparative Examples 1-4 were tested, and the surface resistance of the card protection films was tested. The results are shown in the following table:

[0122] Group Surface resistance(Ω) Example 1 <![CDATA[9.6×10 7 ]]> Example 2 <![CDATA[8.3×10 7 ]]> Example 3 <![CDATA[9.2×10 7 ]]> Example 4 <![CDATA[9.4×10 7 ]]> Example 5 <![CDATA[9.5×10 7 ]]> Comparative Example 1 <![CDATA[6.6×10 9 ]]> Comparative Example 2 <![CDATA[6.8×10 9 ]]> Comparative Example 3 <![CDATA[7.2×10 8 ]]> Comparative Example 4 <![CDATA[7.6×10 9 ]]>

[0123] As can be seen from the above table, the antistatic performance of the card protection film in Examples 1-5 is significantly better than that in Comparative Examples 1-4, which indicates that the adhesive layer containing nano zinc oxide and crystalline hydrate added in the preparation process of the present invention can significantly improve the antistatic performance of the card protection film. Although nano zinc oxide is added to Comparative Example 3, since crystalline hydrate is not added, it does not have a stable H2O molecular environment and the electron decomposition effect is not high. Therefore, although its antistatic performance is better than that of Comparative Examples 1 and 2, it is still significantly worse than that of Examples 1-5. In Comparative Example 4, only crystalline hydrate is added, and there is no electron decomposition effect. The antistatic performance of the final card protection film is the same as that of Comparative Examples 1 and 2.

[0124] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A preparation process of an antistatic card protection film, characterized in that: The specific steps include: A glue layer containing nano zinc oxide and crystalline hydrate is coated on one side of a biaxially stretched polyester base film, and an ethylene-vinyl acetate copolymer layer is coated on the glue layer to obtain a composite film, which is then irradiated with ultraviolet light to obtain the antistatic card protection film; the raw materials of the glue layer also contain polyvinyl alcohol and acrylic resin; the glue layer contains the following raw materials in parts by weight: 100-150 parts of polyvinyl alcohol, 5-10 parts of acrylic resin, 5-15 parts of nano zinc oxide, 10-15 parts of crystalline hydrate and 50 parts of deionized water. -100 parts; the crystalline hydrate is MgCl2·6H2O or Ba(OH)2·8H2O; the material of the biaxially oriented polyester base film comprises polyethylene terephthalate, polybutylene terephthalate or polyethylene naphthalate; the longitudinal stretching ratio of the biaxially oriented polyester base film is 2.4-3.3, and the transverse stretching ratio is 2.7-3.2; the particle size of the nano zinc oxide is 15-25μm, and the particle size of the crystalline hydrate is 50-75μm; the coating method of the adhesive layer is air spraying.

2. A process for preparing an antistatic card protection film as claimed in claim 1, characterized in that: The ultraviolet irradiation treatment uses ultraviolet rays with a wavelength of 350-380nm.

3. An anti-static card protection film, characterized in that: The product is prepared by the process described in any one of claims 1 to 2.

Citation Information

Patent Citations

  • High-quality card protection membrane and preparation method thereof

    CN108394160A

  • Anti-static card protecting film and preparation process thereof

    CN114836144A

  • Electrically conductive adhesive materials

    US4860754A